Banana Pseudostem Waste A Source of Additional Income for Growers - Patil, R. G. (Indian Farming, 2015)
The banana crop, apart from fruit also generates huge quality of biomass in the form of pseudostem, leaves, suckers etc. The pseudostem in particular is an absolute waste in most of the states of India. An array of value added products from banana pseudostem have been developed by the consortium led by NAU, Navsari and financed under NAIP.